The role of salivary antioxidant level in polycystic ovary syndrome women under assisted reproductive technology treatment: A case-control study - Narges Gholizadeh; Maryam Koopaie; Ashraf Aleyasin; Atousa Mortazavi Milani; Marziyeh Aghahosseini; Mohammad Javad Kharrazifard; Mohadeseh Bahmaee (International Journal of Reproductive BioMedicine)
Background: Infertility is defined as the inability to conceive after 12 months of regular unprotected intercourse. Approximately 85% of infertile couples have an identifiable cause, one of the most common causes of infertility is polycystic ovary syndrome (PCOS). The reduction of antioxidant levels in serum and follicular fluid in infertile women compared to healthy women shows the importance of further studying these markers.